Organizational Building Blocks for Blockchain Governance: A Survey of 241 Blockchain White Papers - Honkanen, Petri; Nylund, Mats; Westerlund, Magnus (Frontiers in Blockchain, 2021)
Governance for centralized organizational structures has long roots and well-developed frameworks, including for various specialty areas, such as IT or data governance. However, the introduction of blockchain technology as a supportive tool for implementing decentralized organizations requires a renewed focus for research in the area. The paper utilizes empirical data from blockchain ecosystems in the form of white papers (public communique of intention) to analyze their governance intentions. The empirical findings are based on a review of 241 blockchains and distributed ledger technology white papers, out of which 67 include explicit descriptions of how governance should be organized in the ecosystem. Our empirical research distinguishes between three categories of governance: objectives, mechanisms, and stakeholders. We further identify 28 features for these categories, which are described in an open encoding format. Hence, the paper contributes to the emerging blockchain research field, particularly to the decentralized aspects of blockchain governance research. This research also reveals that blockchain governance does not receive the attention it should as a large majority of ecosystems have not disclosed their governance intentions. The results can be utilized as a framework for future research. The results can also be helpful for industry when designing and developing governance systems.